89.9k views
2 votes
Y = x + 7y = 4y = x + 5y = 3x y = x - 9y = -4xx + 3y = 1y = 2x + 5

User Scarygami
by
4.8k points

1 Answer

5 votes

Given that: y = x + 7

y = 4

y = x + 7

y = 4

substitute the value of y into the above question

4 = x + 7

Isolate x

x = 4 - 7

x = - 3

For the second question

y = x + 5 ------ equation 1

y = 3x ----------equation 2

Substitute the value of y = 3x into the equation 1

3x = x + 5

Collect the like terms

3x - x = 5

2x = 5

Divide both sides by 2

2x/2 = 5/2

x = 5/2

substitute the value of x = 5/2 into the equation 2

y = 3x

y = 3 (5/2)

y = 3 x 5 / 2

y = 15/2

User Waleed Abdalmajeed
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.